Molecular Dynamic Simulations of Carbon and Chlorine Isotopologue Fractionation of Chlorohydrocarbons during Diffusion in Liquid Water - Wanner, Philipp; Hunkeler, Daniel (My University, 2019)
Until now, the magnitude of isotopologue fractionation of organic compounds due to aqueous-phase diffusion has been quantified only experimentally. This study aims to determine the extent of aqueous-phase diffusion-induced isotopologue fractionation of organic compounds for the first time on a computational basis using molecular dynamic simulations (MDS). The MDS were conducted for different organic compounds including chlorinated ethenes (trichloroethene (TCE)) and ethanes (1,2-dichloroethane (1,2-DCA)) and for different isotopologues (carbon and chlorine). The MDS revealed a weak power law mass (m) dependency of the diffusion coefficient (D ∝ m−β with β ≤ 0.049) for carbon and chlorine isotopologues of TCE and 1,2-DCA, consistent with experimental results. The MDS showed that the mass of the diffusing species is the key controlling factor for diffusion-induced isotopologue fractionation and not the molecular volume as suggested by previous studies. Furthermore, the MDS revealed that the weak power law mass dependency of the diffusive transport rate originates from an interplay between strongly mass-dependent short-term and mass-independent long-term solute−solvent interactions. Hence, the presented MDS results provide for the first a time a theoretical rationale for the experimentally observed magnitude of isotopologue fractionation of organic compounds caused by aqueous-phase diffusion.